THE PHILOSOPHICAL FOUNDATIONS OF CULTIVATING COMMUNICATION CULTURE AMONG YOUTH - Egamberdiyeva Nafisa Mustafayevna (Innovate Conferences, 2025)
The development of communication culture among youth is crucial for fostering social harmony, mutual understanding, and personal growth. This paper explores the philosophical foundations of communication culture, examining various ethical theories and their implications for youth education. By analyzing the works of key philosophers and contemporary thinkers, this study aims to provide a framework for nurturing effective communication skills in young individuals. This paper provides a philosophical exploration into cultivating communication culture among youth, emphasizing that nurturing these skills is crucial for both individual development and societal well-being.
Keywords: Intercultural communication, meaning holism, system of beliefs, the teaching of culture.